A projection-based making-human-feel-safe human-robot cooperation system. (2017) - Liu, Diyi; Kinugawa, Jun; Kosuge, Kazuhiro
When a person is working on a human-robot cooperation system, he or she tends to worry about possible collisions with the robot, because of a lack of internal information about the robot. This internal information is, for example, an awareness of a worker's presence or future robot motion. Knowing such internal information, he or she will feel safe since he or she can avoid possible collisions with the robot by foreseeing the motion of the robot. Therefore, this paper proposes a "projection-based making-human-feel-safe human-robot cooperation system" that not only ensures the safety of a human worker but also ensures that the worker feels safe when working with a robot by displaying the internal information of the robot using projection technology. To develop this system, a projector is utilised on a human-robot cooperation system to project the internal information. An elastic band framework was implemented to plan a safe path considering the position of the worker. Finally, an evaluation experiment was conducted to illustrate the effectiveness of the system.